The Related Workplace Indicators to Health of Treatment Staff during the Pandemic in Hospitals Affiliated with Mashhad University of Medical Sciences, Iran - Shapour Badiee Aval; Seyed Javad Hosseini; Javad Mahmoudi Fathabadi; Maryam Yaghoobi; Golnaz Sabouri; Zeinab Sadat Hosseini; Mohammadhasan Ezzati; Zohreh Rokni; Sedigheh Mohammadnezhad Ostad; Homa Sotvan; Mohsen Shirazi Mehrabad; Mahdieh Farhanji (Patient Safety and Quality Improvement Journal)
Introduction:In the conditions of disease crisis, workplace indicators play an important role in improving the provision of medical services. This study aimed to evaluate an association between workplace indicators and the health of treatment staff during pandemics in hospitals affiliated with Mashhad University of Medical Sciences. Materials and Methods: This cross-sectional study was conducted on healthcare workers with covid-19 infection during the pandemic in hospitals affiliated with Mashhad University of Medical sciences. The data collection tool was the standard “quality of work-life” questionnaire. The validity of this questionnaire was obtained at 0.85. Data were analyzed using analytic statistical tests (chi-square) and descriptive (mean and standard deviation) and using SPSS version 16. Results: A total of 442 treatment staff participated in this study, and 230 (52.1%) were women. The mean age was 29.2±9.2 years. The average work history, the average working hours per week, and the average workplace indicators scores were 7.22±10.47, 46.49±12.67, and 109.11±75.46, respectively. The mean quality of work-life score was in the moderate range. There was a statistical association between the mean quality of work-life score with working hours and workplace unit (p<0.001). There was no statistical relation between other variables and to quality of work-life score (p>0.05). Conclusion:The results indicated that improving workplace indicators is effective in the health of treatment staff and the provision of health services.